Knowledge improvement and social benefits among STCP farmer field school participants in Cameroon - David, S. (2007)
Gaps in the farmer field school literature and mixed results do not allow for conclusions to be reached about the efficacy of the approach, especially in Africa where there are few mature farmer field school (FFS) programs. A case study of farmers who attended cocoa integrated crop and pest management (ICPM) farmer field schools operated by the Sustainable Tree Crops Program (STCP) in Cameroon and non-participating farmers provides empirical evidence on three issues: the effectiveness of FFS training, the potential contribution of farmer-to-farmer diffusion to the scaling up process and social impact. Cameroonian data show positive results that confirm the power of discovery learning. FFS provided farmers with new skills and knowledge on cocoa ICPM and FFS graduates demonstrated superior knowledge on cocoa ICPM generally compared to non-FFS farmers. However, the tendency of FFS participants to retain and diffuse new skills and practices more than concepts and principles suggests the need to review aspects of the training. Forty nine FFS graduates spontaneously provided hands-on informal training to 193 other farmers on key ICPM practices, demonstrating the tremendous potential contribution of farmer-to-farmer diffusion to scaling up farmer training. The case study shows that FFS can be a starting point for farmer empowerment, but suggests that social and technical outcomes can only be sustained if the appropriate local and national level institutions, support systems and policy framework in relation to agricultural extension and research are developed. The paper also highlights methodological issues related to measuring the social impacts of FFS.